The miRNA 361-3p, a Regulator of GZMB and TNF Is Associated With Therapeutic Failure and Longer Time Healing of Cutaneous Leishmaniasis Caused by L. (viannia) braziliensis - Lago, Tainã S.; Silva, Juliana Almeida; Lago, Ednaldo L.; Carvalho, Edgar M.; Zanette, Dalila L.; Castellucci, Léa Cristina (Frontiers in Immunology, 2018)
L. (viannia) braziliensis infection causes American Tegumentary Leishmaniasis (ATL), with prolonged time to healing lesions. The potent inflammatory response developed by the host is important to control the parasite burden and infection however an unbalanced immunity may cooperate to the tissue damage observed. The range of mechanisms underlying the pathological responses associated with ATL still needs to be better understood. That includes epigenetic regulation by non-coding MicroRNAs (miRNAs), non-coding sequences around 22 nucleotides that act as post-transcriptional regulators of RNAs encoding proteins. The miRNAs have been associated with diverse parasitic diseases, including leishmaniasis. Here we evaluated miRNAs that targeted genes expressed in cutaneous leishmaniasis lesions (CL) by comparing its expression in both CL and normal skin obtained from the same individual. In addition, we evaluated if the miRNAs expression would be correlated with clinical parameters such as therapeutic failure, healing time as well as lesion size. The miR-361-3p and miR-140-3p were significantly more expressed in CL lesions compared to normal skin samples (p = 0.0001 and p < 0.0001, respectively). In addition, the miR-361-3p was correlated with both, therapeutic failure and healing time of disease (r = 0.6, p = 0.003 and r = 0.5, p = 0.007, respectively). In addition, complementary analysis shown that miR-361-3p is able to identify with good sensitivity (81.2%) and specificity (100%) patients who tend to fail initial treatment with pentavalent antimonial (Sbv). Finally, the survival analysis considering “cure” as the endpoint showed that the higher the expression of miR-361-3p, the longer the healing time of CL. Overall, our data suggest the potential of miR-361-3p as a prognostic biomarker in CL caused by L. braziliensis.